A new metaheuristic optimization method: the algorithm of the innovative gunner (AIG). Issue 12 (2nd December 2019) - Pijarski, Paweł; Kacejko, Piotr
ABSTRACT: This article presents a new method of metaheuristic optimization, the algorithm of the innovative gunner (AIG), inspired by the choice of artillery parameters that sends a shot precisely to a target. The applied correction of the cannon's setting parameters differs from that defined by classic artillery theory. The innovativeness of the AIG results from the fact that at each step of the iterative process, the previous solution is corrected by means of specially selected multiplication factors. This is a major difference from most methods in which, at each successive step, a corrective element is added to the previous solution. The AIG is characterized by high efficiency and speed in solving various optimization problems having nothing to do with ballistics. It is extremely simple in description and implementation. The algorithm was tested on several known test-optimization tasks. The results are noticeably better than those achieved by other methods and prove the practical usefulness of the AIG.